Calamitic liquid crystals involving fused ring and their metallomesogens. Issue 2 (17th August 2017) - Thaker, Bharat; Limbachiya, Nilesh; Patel, Kalpesh; Patel, Neeraj
Abstract : In this paper, the authors report two different types of terminally substituted homologous series with an ester–azo central linkage involving fused-ring achiral liquid crystals such as 4-((4-chlorophenyl)diazenyl)-3-hydroxyphenyl 6-alkoxy-2-naphthoate (series A) and 4-((4-nitrophenyl)diazenyl)-3-hydroxyphenyl 6-alkoxy-2-naphthoate (series B). Their copper (II) metallomesogens were synthesised and characterised by methods such as elemental analysis, Fourier transform infrared, proton ( 1 H) nuclear magnetic resonance (NMR), carbon-13 ( 13 C) NMR and mass spectroscopic studies. Thermotropic properties were studied by performing polarising optical microscopy and DSC analysis. All liquid crystalline compounds (ligands) display nematic and/or smectic phase/s. Unlike ligands, both types of copper (II) complexes show a solely nematic behaviour. The series B exhibit Sm-form from C7 derivatives where as series A exhibit Sm-form from C8 derivatives. The series B is more thermally stable than series A. The series A exhibit monotropic nematic phase for C4 derivative and monotropic smectic phase for C10 derivative. Whereas series B display monotropic nematic phase for C5 derivative and C12 derive is fully monotropic i.e. both nematic and smectic phase obtained only on cooling cycle.